FOSTERING VOCABULARY EXPANSION IN READING ACTIVITIES IN A FOREIGN LANGUAGE - Ruzmetova Dildora Adilbekovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study explores theoretical and psycholinguistic foundations, word-formation processes (derivation, conversion, compounding), and vocabulary classification by function, frequency, semantics, and difficulty. Pedagogical strategies such as extensive reading, morphological analysis, contextual learning, lexical chunks, and communicative practice are shown to enhance lexical competence. Integrating inferential approaches into instruction promotes learner autonomy, analytical thinking, and the transition from receptive to productive vocabulary, fostering linguo-cognitive competence.